Managing Youth Risk Behavior Through Parental Involvement and Character Education: Implications for Human Capital Development in Emerging Communities - Sididi; Salju; Rismawati; Pahala, Indra (Fakultas Ekonomi, Universitas Negeri Jakarta, Indonesia, 2025)
This study explores how parental involvement and character education operate as strategic instruments of Human Resource Development (HRD) in preventing adolescent drug abuse. Employing a qualitative-descriptive approach, data were collected from 15 adolescents and their parents in Palopo, Indonesia. Thematic analysis revealed that peer influence, emotional neglect, and the absence of structured value education were key factors contributing to youth vulnerability. In contrast, families practicing consistent value transmission, emotional support, and dialogic parenting enhanced adolescent behavioral resilience. The findings position the family as a foundational site of early-stage HRD, where emotional intelligence, moral reasoning, and decision-making competencies are developed. The study offers practical implications for HRD policy and practice, emphasizing the integration of family-based interventions and value-oriented parenting in national strategies to strengthen youth behavior and human capital in emerging communities